2003
DOI: 10.1111/j.1432-1033.2003.03890.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of maize lysine metabolism and endosperm protein synthesis by opaque and floury mutations

Abstract: The capacity of two maize opaque endosperm mutants (o1 and o2) and two floury (fl1 and fl2) to accumulate lysine in the seed in relation to their wild type counterparts Oh43+ was examined. The highest total lysine content was 3.78% in the o2 mutant and the lowest 1.87% in fl1, as compared with the wild type (1.49%). For soluble lysine, o2 exhibited over a 700% increase, whilst for fl3 a 28% decrease was encountered, as compared with the wild type. In order to understand the mechanisms causing these large varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0
31

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 45 publications
4
63
0
31
Order By: Relevance
“…The lysine content in fl1 mutants and wild-type maize is usually about 2%, and reaches approximately 4% of total protein, in fl2 and o2 mutants (Weizmann, 1998). Azevedo et al (2003) also showed fl2 and o2 mutants to be higher in lysine content (3.8% of total protein) than fl1, and fl1 to be most similar to, wild-type maize (1.9 vs. 1.5% of total protein, respectively). Levels of lysine from our study were somewhat higher than those of fl1 genotypes reported in the above studies; however, the majority of floury OPV lysine values were only about 10% higher those of the dent or flint OPVs we examined.…”
Section: Accessionmentioning
confidence: 99%
“…The lysine content in fl1 mutants and wild-type maize is usually about 2%, and reaches approximately 4% of total protein, in fl2 and o2 mutants (Weizmann, 1998). Azevedo et al (2003) also showed fl2 and o2 mutants to be higher in lysine content (3.8% of total protein) than fl1, and fl1 to be most similar to, wild-type maize (1.9 vs. 1.5% of total protein, respectively). Levels of lysine from our study were somewhat higher than those of fl1 genotypes reported in the above studies; however, the majority of floury OPV lysine values were only about 10% higher those of the dent or flint OPVs we examined.…”
Section: Accessionmentioning
confidence: 99%
“…Além destes resultados foi constatado que os teores dos demais aminoácidos apresentaram variações, com redução ou aumento, dependendo do aminoácido analisado e do mutante (AZEVEDO et al, 2003;HUNTER et al, 2002). Esses dados mostram que os eventos aqui transformados possuem potencial para grãos com alta lisina, já que foram encontrados aumentos nos teores de lisina solúvel e diminuição na concentração das zeínas II.…”
Section: Discussionunclassified
“…O aminoácido lisina provocou a maior inibição da atividade total de AK, indicando a predominância da isoforma sensível a este aminoácido. A inibição causada pela presença de lisina e treonina mostrou um efeito aditivo na inibição da atividade da enzima, isto é, houve a soma da inibição dos aminoácidos, como já observado anteriormente em trabalhos com mutantes para alta lisina (AZEVEDO et al, 2004). Estes resultados estão de acordo com o mecanismo de regulação por retroalimentação, característico de enzimas alostéricas em vias de biossíntese, citadas para milho em inúmeros trabalhos (AZEVEDO et al, 1992;AZEVEDO et al, 2006).…”
Section: Discussionunclassified
See 2 more Smart Citations